2019
DOI: 10.2337/dc18-1838
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate, Autonomic Function, and Future Changes in Glucose Metabolism in Individuals Without Diabetes: The Whitehall II Cohort Study

Abstract: Short running title: Autonomic function and glucose metabolism in non-diabetic individuals Word count: Main text: 3296, Abstract: 247 Number of Figures and Tables: 2 tables (2 supplementary tables). 1 figure (1 supplementary figure). Abbreviations CAN: cardiovascular autonomic neuropathy HF power: high-frequency power HR: heart rate HRV: heart rate variability HsCRP: high-sensitivity C-reactive protein LF power: low-frequency power LH/HF ratio: low frequency / high frequency power ratio IL-6: Interleukin 6 IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 42 publications
2
15
1
Order By: Relevance
“…It has been suggested that autonomic dysfunction causes hyperglycemia via impaired insulin release by the pancreas, increased glucose production by the liver, and impaired glucose uptake and insulin resistance in skeletal muscles (32). Indeed, several studies have shown that cardiac autonomic dysfunction measured by high heart rate or low HRV is associated with incident type 2 diabetes (33,34). Hence, it is possible that a vicious cycle of hyperglycemia and cardiac autonomic dysfunction exists.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that autonomic dysfunction causes hyperglycemia via impaired insulin release by the pancreas, increased glucose production by the liver, and impaired glucose uptake and insulin resistance in skeletal muscles (32). Indeed, several studies have shown that cardiac autonomic dysfunction measured by high heart rate or low HRV is associated with incident type 2 diabetes (33,34). Hence, it is possible that a vicious cycle of hyperglycemia and cardiac autonomic dysfunction exists.…”
Section: Resultsmentioning
confidence: 99%
“…We are therefore unable to comment on whether similar sex differences also exist in patients with cardiac and/or autonomic abnormalities (e.g. diabetic patients [30]). Likewise, since the data were obtained in primarily middle-aged adults, we are unable to comment on sex differences in healthy children or in the advanced age elderly [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…This study has several limitations, including the cross-sectional design, which negates the ability to demonstrate causal relationships, a major shortcoming of this trial. Thus far, only a single report [ 47 ] has shown that resting heart rate in individuals without diabetes is associated with future unfavorable changes in insulin levels and insulin sensitivity. Although those results were inconclusive, the authors speculated that the associations may be mediated by autonomic function.…”
Section: Discussionmentioning
confidence: 99%